Locals perception on the economic and social impacts of the propose Labuan - Menumbok Bridge: a case study in Kg. Durian Tunjung, Labuan F.T. / Ani Juaini Bahrin - Bahrin, Ani Juaini (2010)
In order to achieve the status of developed country, Malaysian government had done so many things especially in term of development facilities provides to the people. Many government projects such as hospitals, police station, tall buildings and so forth had been built in order to fulfill the needs of the Malaysians. Therefore, this study is also focus on one of the proposed government projects which is the Proposed Labuan - Menumbok Bridge. This study aims to see the perception among the locals towards the impacts of the bridge in term of economic and social that will be face by the locals itself. With the existence of this study, it was hope that the government can see the importance to take the locals views towards any government project as the findings would be useful for the respective parties in order to evaluate the favorable of each project to the government and to the people itself as a whole.